Direct mixed-quantum/classical computations of k(T). An analysis of the use of different coordinate systems - Clavero, Esteban Dario (2011)
We have obtained three mixed-quantum/classical schemes to directly calculate thermal rate constants through the evaluation of flux-flux correlation function. These schemes are appropriate to treat three-atom reactions, but could be easily extended to larger systems. One of the schemes uses normal mode coordinates, defined at the transition state. The others use hyperspherical coordinates. The proposed algorithms were applied to the H + H2 → H2 + H reaction, and their accuracy was tested by comparison with full-quantum results. In this article, we present the derivation of the three mixed-quantum/classical schemes, describe the details of their implementation, and discuss the quality of their results.